Transmission and Treatment of Covid-19 Disease in Young Children (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article is about how to deal with coronavirus like a child. And what should be paid attention to in the prevention, treatment and treatment of the disease.